Youtube As A Resource In Facilitating Esl Teaching And Learning Experiences - Morat, Berlian Nur (2013)
Due to the challenging nature of teaching English as second language (ESL) learners, ESL instructors are constantly looking for fresh idea and innovative teaching materials as one of the means to enhance the teaching and learning. In harmony with today’s technology driven world, the incorporation of video into the lessons is one of the instances. As the leading and web’s largest video sharing website, YouTube is increasingly being used by ESL instructors as a pedagogical resource. In this research, an advocate of this practice was identified and her experience in using YouTube as a resource to facilitate ESL teaching and learning in a Malaysian higher learning institution context was explored. Since her ESL learners were also directly involved, their experiences of undergoing lessons which incorporated YouTube were discovered as well. Conducted in a full qualitative manner, the experiences were uncovered through a series of journal entries by the ESL instructor and seven of her learners as well as in-depth interviews with them. A number of classroom observations of the lessons were also carried out to further examine the implementation. Through thematic data analysis, the findings demonstrated the potential of YouTube incorporation in the lessons in fostering a creative, borderless and authentic ESL teaching and learning. Moreover, the impacts as perceived by the participants indicated the potential of its incorporation in enhancing the ESL learners’ language skills as well as the motivation in learning the language. Unexpectedly, the learners were found to learn not only content based knowledge yet also technological and life related skills. Furthermore, another unique finding is the continuous practice despite the challenges and difficulties faced by the participants. The drawbacks discovered in this very research, in a way, suggested rooms for improvements. The recommendations drawn from the conclusions and implications of the study would hopefully implicate the ESL pedagogical practice and future research positively.